Antioxidant activity of silver nanoparticles synthesized using Tulak wood leaf extract (schefflera elliptica harms) - Aryasa, I Wayan Tanjung; Artini, Ni Putu Rahayu (Universitas Ahmad Dahlan, 2025)
Nanoparticles have been used in therapies applied to target specific parts. By delivering electrons to free radicals, silver nanoparticles (AgNPs) can reduce their activity and stop a chain reaction that would otherwise result in the creation of more free radicals. But the most common way to create silver nanoparticles is to use a variety of organic and inorganic reducing agents to chemically reduce silver precursors, usually silver salts. Various stabilizing or capping agents are frequently used to this process. Green synthesis and other ecologically friendly synthesis techniques are becoming more popular for producing metal nanoparticles that adhere to biodiversity principles. Accordingly, this study has determined that the tulak tree is a plant that effectively reduces green space. This study uses different concentrations of AgNO3 solution at 1 mM and 2 mM. A Particle Size Analyzer's (PSA), The distribution of sizes of the artificially produced AgNPs was examined. The particles measuring between 1 and 100 nm made from the Tulak wood leaf extract with the corresponding AgNO3 concentrations had average diameters of 88.2 nm and 16.9 nm. AgNPs were also shown to exist in a range of shapes, encompassing sphere, hexagonal, and triangular ones, according to Transmission Electron Microscopy (TEM) examination. Antioxidant qualities are displayed by AgNPs made with Tulak wood leaf extract. These antioxidant properties were assessed utilizing DPPH, which has 517 nm is the greatest absorption. Furthermore, the antioxidant activity's outcomes tests show that the AgNPs made using Tulak wood leaf extract biosynthesis have comparatively low antioxidant activity.